Evaluation of teaching performance in the learning achievement of the mathematics area (Revista de Psicología, 2020)
This study aims to analyze the evaluation of teacher performance in the achievement of learning in the area of mathematics in children of the primary level. A non-experimental design of causal descriptive type is used. The population participating in the study was composed of 15 teachers and 130 students of regular basic education. The instrument used is a scale of evaluation of teaching performance of 23 items distributed in 4 dimensions: preparation for student learning, teaching for student learning, participation in the management of the school articulated to the community and development of the professionalism and the teaching identity. The psychometric properties indicated that it is valid and reliable. The results confirm that there is a significant relationship between the evaluation of teacher performance and learning achievement in the area of mathematics. A significant positive statistically significant linear association was found (P = 0.873, p
Keywords: Teaching performance; learning achievement; primery level; mathematics